Analysis of Production Cost Control for Determining Selling Prices at UD. Mansur Furnitur - Putri Annisa Dewi; Muh Rum; Amril Amril (Income Journal Of Economics Development, 2026)
This research aims to determine the implementation of UD production cost control. Mansur in determining the right selling price so as to increase production efficiency. This research uses a quantitative descriptive approach. The data sources used are primary and secondary data. The data analysis technique used in this research is Standard Costing Analysis (Variance Analysis). The results of this research show that the total production costs according to UD. Mansur before controlling costs amounting to Rp. 31,352,250 per 10 units with a price per unit of Rp. 3,135,225. after researching by looking at the standards and realization of Rp. 29,690,125 with a price per unit of Rp. 2,969,012.5. UD. Mansur has not controlled costs well, but the results of this research can provide input to UD management. Mansur reduces production costs by carrying out variance analysis.